Loss of nuclear expression of the p33ING1b inhibitor of growth protein in childhood acute lymphoblastic leukaemia. Issue 8 (1st August 2002) - Nouman, G S; Anderson, J J; Wood, K M; Lunec, J; Hall, A G; Reid, M M; Angus, B
Abstract : Background/Aims: p33 ING1b is a tumour suppressor protein involved in growth control and apoptosis. Suppression of p33 ING1b expression is associated with the loss of cellular growth control and immortalisation, whereas its overexpression causes cell cycle arrest. Moreover, normal p33 ING1b expression is essential for optimal function of p53. Acute lymphoblastic leukaemia (ALL) is the most common malignancy of childhood, accounting for one third of all childhood malignancies. A variety of cytogenetic abnormalities have been described but there is no single abnormality common to all cases. Deregulation of the TP53 pathway is a common genetic abnormality in human malignancies. However, TP53 mutations are uncommon in ALL. It is possible that alternative mechanisms of regulation of the TP53 apoptosis pathway, such as modulation of p33 ING1b expression, may be important in ALL. The aim of this study was to assess the expression of p33 ING1b in childhood ALL. Methods: One hundred and forty five patients with childhood ALL were investigated in this immunohistochemical study of the expression of p33 ING1b . Results: Loss of nuclear expression of p33 ING1b was seen in 78% of cases. This was associated with increased cytoplasmic expression of the protein. Kaplan Meier survival analysis demonstrated a trend towards a better prognosis for patients with tumours that had lost nuclear p33 ING1b . Conclusion: These results suggest that the loss of nuclear p33 ING1b expression may be an important molecular event in the pathogenesis of childhood ALL.